Semiotic Analysis of Social Class Representation in Satria Dewa Gatotkaca Movie: Analisis Semiotika Representasi Kelas Sosial dalam Film Satria Dewa Gatotkaca - Hidayatullah, Barriman; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2025)
The study aims to analyze the representation of social class in the film